PERAN KEPALA MADRASAH DALAM MENINGKATKAN KEDISIPLINAN PESERTA DIDIK DI MADRASAH IBTIDAIYAH HIDAYATUL MUBTADI’IN TASIKMADU MALANG - Nia Meiliya Permata; Mohammad Afifulloh; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
In an educational institution, the headmaster is a very decisive foundation for the achievement of any organizational goals and any form, as well as in the form of education. The headmaster has an important role in an educational institution. Then this madrasah head is a leader who must produce good quality education. So, to achieve this educational goal, it is necessary to have the role of the madrasa head in improving the discipline of students in MI Hidayatul Mubtadi’in Malang. From the results of the study it was concluded that the headmaster of madrasa to improve student discipline in MI Hidayatul Mubtadi'in Malang. The madrasah head tries to strengthen the madrasa rules and knowledge to behave according to the morality of the karimah by approaching, accustoming and giving examples, invitations, and move the rules / order and conduct monitoring, evaluation of student discipline. Therefore the madrasa head and madrasa should increase their responsibilities especially in improving time discipline because it is closely related to the learning process. From there, it can bring Madrasah Ibtidaiyah Hidayatul Mubtadi'in Malang to become a higher quality and better madrasah.